14C Allocation in tree–soil systems - Paul, Eldor A., author; Pregitzer, Kurt S., author; Horwath, William R., author; Heron Publishing, publisher (Colorado State University. Libraries, 1994)
We studied whole-tree C allocation with special emphasis on the quantification of C allocation to roots and root respiration. To document seasonal patterns of C allocation, 2-year-old hybrid poplar trees greater than 3 m tall were labeled with 14CO2 in a large Plexiglas chamber in the field, in July and September. Climate and CO2 concentration were controlled to track ambient conditions during labeling. Individual tree canopy CO2 assimilation averaged 3.8 μmol CO2 m−2 s−1 (12.9 g C day−1 tree−1) in July and 6.2 μmol CO2 m−2 s−1 (9.8 g C day−1 tree−1) in September. Aboveground dark respiration was 12% of net daytime C fixation in July and 15% in September. Specific activity of root–soil respiration peaked 2 days after labeling and stabilized to less than 5% of maximum 2 weeks later. Low specific activity of root–soil respiration and a labeled pool of root C demonstrated that current photosynthate was the primary source of C for root growth and maintenance during the growing season. Root respiration averaged 20% of total soil respiration in both July and September based on the proportion of labeled C respired to labeled C fixed. In July, 80% of the recovered 14C was found above ground and closely resembled the weight distribution of the growing shoot. By September, 51% of the recovered 14C was in the root system and closely resembled the weight distribution of different size classes of roots. The finding that the distribution of biomass and 14C were similar verified that the C introduced during labeling followed normal seasonal translocation pathways. Results are compared to smaller scale labeling studies and the suitability of the approach for studying long-term C fluxes is discussed.
Keywords: poplars; respiration; roots; whole-tree carbon allocation; biomass; growth